THE RIGHT TO PHYSICAL EDUCATION OF PERSONS WITH DISABILITIES. INDICATORS OF THEIR EFFECTIVE IMPLEMENTATION IN EDUCATIONAL ORGANIZATIONS. (Fiep Bulletin - online, 2016)
This article presented shows results of research conducted by the Universidad Nacional La Matanza aimed to recognize institutional characteristics presented by organizations including educational, when developing a physical education adapted to people with disabilities. In order to provide contributions to ensure that institutions can guarantee the human right to adapted physical education, this paper describes a set of indicators to recognize human resources, skills and infrastructure adaptations, required for its effective implementation.
Keywords: .